In Vivo Simultaneous Imaging of Plasma Membrane and Lipid Droplets in Hepatic Steatosis using Red-Emissive Two-Photon Probes - Lee, Hyo Won; Pati, Tanmay Kumar; Lee, In Jeong; Lee, Jeong Mi; Kim, Bo Ra; Kwak, Sun Young; Kim, Hwan Myung (Analytical Chemistry, 2022)
The plasma membrane, which is a phosphoglyceride bilayer at the outer edge of the cell, plays diverse and important roles in biological systems. Visualization of the plasma membrane in live samples is important for various applications in biological functions. We developed an amphiphilic two-photon (TP) fluorescent probe (THQ-Mem) to selectively monitor the plasma membrane in live samples. This probe exhibited red emission (620-700 nm), large TP absorption cross sections (δmax > 790 GM), and high selectivity to the plasma membrane. In cultured cells and in vivo hepatic tissue imaging, THQ-Mem showed bright TP-excited fluorescence (TPEF) and remarkable selectivity for the plasma membrane. Furthermore, simultaneous in vivo imaging with THQ-Mem and a TP lipid droplet probe could serve as an efficient tool to monitor morphological and physiological changes in the plasma membrane and lipid droplets.
Keywords: Bi-layer; Biological functions; Hepatic steatosis; In-vivo; Lipid droplets; Phosphoglycerides; Red emissive; Simultaneous imaging; Two photon; Two-photon probes